Relasi Agama dan Kekerasan - Amir Mu'allim (Unisia, 2006)
At least there are two perspectives regarding the religion affairs, firstly, religion is as doctrine, secondly, religion is as the product of human understanding of religion doc trine. In this connection, religion as doctrine has principies, for examples justice, equality, plurality, freedom, democracy, and humanity. These principles are stabil, immutable, not change. But, those principles should be applied to human life wisely. Thus, the violences (terrorism,Jihad, atc) that related to and in the name of religion should be understood comprehensively carefully because they include and be a part of religion as ideology.